KONTRIBUSI ILMU AL-MUNASABAH TERHADAP KONSISTENSI PESAN DAKWAH DALAM SURAH MAKKIYAH - Selfa Rosmita; Achmad Abubakar; Halimah Basri (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The science of Munasabah is a branch of Qur'anic jurisprudence that examines the interconnectedness and harmony of meaning between verses and suras in the Quran. This study aims to analyze the contribution of the science of Munasabah to the consistency of the da'wah message in the Makkiyah Surahs, particularly regarding key themes such as monotheism, prophecy, and the Day of Resurrection. This study employed a descriptive qualitative approach with library research methods. Data were collected through a review of classical and contemporary tafsir books, as well as the latest scientific literature relevant to the concept of munasabah and Qur'anic da'wah. The analysis was conducted thematically to identify patterns of verse relationships and meaning structures that reinforce the da'wah message. The results show that the science of Munasabah plays a crucial role in maintaining the coherence and unity of the da'wah theme in the Makkiyah Surahs. The logical interconnectedness between verses creates a continuous argumentation that reinforces the message of monotheism and the faith of Muslims in the early days of the prophethood. Munasabah also proves that the Qur'anic revelation is systematically structured and free from contradictions, allowing the message of da'wah to be conveyed rationally, persuasively, and contextually. Thus, the science of al-Munasabah not only reveals the miraculous aspects and rhetorical beauty of the Qur'an but also strengthens the effectiveness of Islamic da'wah as a complete and continuous system of theological communication.